Attitudes toward aging of health professions students: Implications for geriatrics education. Issue 4 (2nd October 2021) - Jester, Dylan J.; Hyer, Kathryn; Wenders, Anna; Andel, Ross
ABSTRACT: We compared attitudes toward aging of students from several health professions (N = 1, 156: 286 medical, 275 pharmacy, 213 undergraduate nursing, 160 graduate nursing, 139 Internal Medicine residents, 49 physical therapy, and 34 physician assistant), and assessed the construct validity of the Image of Aging Scale. Physical therapy and graduate nursing students reported more positive attitudes toward aging in comparison to all other health professions (all p <.001). Differences in attitudes were not strongly affected by demographic variables, clinical exposure, desire to pursue primary care, or interest in providing care to older adults. The Image of Aging Scale yielded good internal reliability and adequate construct validity for health professions students. Health professions students' attitudes toward aging largely reflect the students' professional training, rather than student characteristics or career goals. The Image of Aging Scale is a robust measure of attitudes toward aging in health professions students and in older adults.